The Role of Work Competence and Compensation on Increasing Organizational Commitment - Baidun, Akhmad; Kurnia, Adil; Nofriza, Fatma (Journal of Management, 2024)
Organizational commitment is a crucial factor influencing employee retention and performance. This study aims to investigate the impact of work competence and compensation on enhancing organizational commitment within the workplace.This quantitative research employed multiple regression analysis to examine the relationships between work competence, compensation, and organizational commitment. Data were collected through structured questionnaires distributed to a sample of employees. The validity and reliability of the measurement instruments were ensured, and the data were analyzed using t-tests, ANOVA, and regression analysis.The findings reveal that work competence has a significant positive effect on organizational commitment (t = 2,569, p = 0,012). In contrast, compensation does not show a significant impact on organizational commitment (t = 1,095, p = 0,276). The regression model explains approximately 47,8% of the variance in organizational commitment, with an adjusted R Square of 46,8%, indicating that the model is reasonably effective in capturing the influence of work competence and compensation on organizational commitment. The study concludes that work competence significantly contributes to increasing organizational commitment, while compensation does not have a significant effect in this context. Organizations should prioritize enhancing employees' work competence as a strategy to foster higher levels of organizational commitment. Further research is recommended to explore additional factors influencing organizational commitment and to validate these findings in different contexts.